2020
DOI: 10.4038/slja.v28i2.8515
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of differential brachial plexus block using ropivacaine in intraoperative conscious patients: A randomized control trial

Abstract: Background: During orthopaedic surgical procedures such as trigger finger repair or tendon repair, differential nerve block (DNB) can permit intraoperative assessment of adequacy of surgery. The current study was undertaken to compare the efficacy and safety of 0.15% ropivacaine and 0.1285% ropivacaine in producing DNB for hand surgeries. Methods: This was a randomized controlled trial of 40 participants, aged 18-60 years, either gender, ASA I/II requiring hand or forearm surgery. Participants were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In clinical practice, BPB can be achieved through several routes, including interscalene, costoclavicular space, supraclavicular, and axillary approaches ( Bhat et al, 2020 ; Jones et al, 2020 ; Mojica et al, 2022 ). The diffusion rate of local anesthetics, the speed of vascular absorption, and the blocking sequence are different for different approaches, which will influence the effects of brachial plexus block ( Wenwen et al, 2016 ; Safa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In clinical practice, BPB can be achieved through several routes, including interscalene, costoclavicular space, supraclavicular, and axillary approaches ( Bhat et al, 2020 ; Jones et al, 2020 ; Mojica et al, 2022 ). The diffusion rate of local anesthetics, the speed of vascular absorption, and the blocking sequence are different for different approaches, which will influence the effects of brachial plexus block ( Wenwen et al, 2016 ; Safa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion rate of local anesthetics, the speed of vascular absorption, and the blocking sequence are different for different approaches, which will influence the effects of brachial plexus block ( Wenwen et al, 2016 ; Safa et al, 2021 ). Studies have found that different approaches may produce different blocking effects even using the same concentration and dose of ropivacaine ( Bhat et al, 2020 ; Jones et al, 2020 ). Additionally, the volume of ropivacaine used for brachial plexus blocks also varies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations